Country or leader?: political change and UN general assembly voting - Dreher, Axel; Jensen, Nathan M. (KOF working papers, 2009)
In this project we explore the relationship between leader change and relations between states. Voting in the United Naion's General Assembly (UNGA) is often used as a measure of political proximity between countries. We use UN voting coincidence to examine how changes in leadership affect relations. Specifically, we examine how political change affects a country’s voting with the United States. In this paper we explore how leadership change affects UNGA voting. Using differences between “key” and “non-key” UN votes to the United States, we explore if political change is driven by preference change or by a changing external position. While political change has little impact on voting on non-key issues (state preferences) we find that after leadership change, countries are more likely to vote in line with the United States on key UN votes. -- United Nations General Assembly voting ; key votes
Keywords: Vereinte Nationen -- Generalversammlung; Arbeitspapier; Graue Literatur